Mahatma Gandhi : Father of the Nation - Anita Ganeri (Hachette, 2010)
Mohandas Karamchand Gandhi, or 'Bapu' as he is fondly called, is known as the Father of the Nation and the greatest leader of the millennium. He took on the might of the British Empire and helped India walk the road to freedom. Through his ideas of peace and non-violence, he changed the history of our country and influenced millions of people not only in India but around the world. Join the curious and playful Digby and his big sister Hester as they make their way through the odds and ends at Mr Rummage's stall at Knick-Knack Market. Discover the wonderful little objects they pick up and enjoy the stories about the great people they belong to.